PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBASIS JAS (JELAJAH ALAM SEKITAR) DALAM PEMBELAJARAN SAINS DI MADRASAH IBTIDAIYAH - Ummu Khairiyah; Roudhotul Ilmiyah; Afifatus Sa’adah (Universitas Islam Lamongan, 2018)
The research objective is to describe the activities of students during the learning process that uses the Contextual Teaching and Learning (CTL) approach based on Jelajah Alam Sekitar (JAS) and determine students' responses to learning using the JAS-based CTL approach. Research is a descriptive quantitative research that uses survey methods and literature studies. The learning activities with CTL approach based on the Jelajah Alam Sekitar (JAS) in science or IPA is a group discussion, direct observation, practicum, game, and final/ test. Where through these activities in accordance with the principles of the JAS approach which consists of exploration, constructivism, the scientific process, learing community, bioedutainment and authentic assessment. So that the learning process based on Student Centered Learning is no longer Teacher Centered Learning which can make students 'scientific skills honed. Students' responses to learning with the CTL approach based on Jelajah Alam Sekitar (JAS) is 89% in the good category (interest and very interest).